Paclobutrazol Improves The Agronomic Performance and Micromorphological Profile of Five Local Black Rice ( Oryza sativa L.) Varieties in Central Java Indonesia (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Local black rice (Oryza sativa L.) is one of the biodiversity of rice in Indonesia, which has tall stature and long cultivation period, easy to lodge, and requires more intensive care. Paclobutrazol (PBZ) is a plant growth inhibitor compound that could reduce plant height and accelerate plants entering the generative phase. This study aimed to determine the effects of PBZ concentration on the agronomic character and micromorphological profile of five local black rice varieties. This research was conducted experimentally using a completely randomized factorial design. The first factor was the local black rice variety (Brebes, Klaten, Magelang, Pati, and Pekalongan ), while the second was PBZ concentration (0, 100, 200, and 300 ppm) with three replications. PBZ spraying was conducted in the fourth week after planting. The data obtained were analyzed using ANOVA and HSD test (α=5%). The results showed that the concentrations of PBZ 300 ppm produced the heaviest 100 grains. The Klaten variety had wide abaxial stomata, the Magelang variety had high abaxial stomata density, while the Pati variety had long abaxial stomata and heaviest 100 grains. The interaction between Brebes variety and PBZ 0 ppm produced high adaxial stomatal density, Klaten variety, and PBZ 100 ppm have vast adaxial stomatal and high abaxial trichome density. Pati variety and PBZ 0 ppm had the most tillers, while Pati variety and PBZ 100 ppm had long adaxial stomata and the most grains per panicle. The study's critical findings are that PBZ gives different micromorphology improvements and increases agronomic performance in local black rice.